Conflict and comedy. Insults, threats, and slapstick in the plays of Aristophanes - Donelan, J. F. (2019)
This thesis examines the form and function of insults, threats, and aggressive slapstick in the comedies of Aristophanes. It seeks to fill a gap in our understanding of Aristophanes’ dramatic technique by considering how conflict between characters serves as a vehicle for humour.